The Effect of Production-Based Learning, Industrial Internship, and Parental Support on Students' Interest in Entrepreneurship in Vocational High Schools - Sri Rahayu Lestari, A.; Jamaluddin, Jamaluddin; Arfandi, Anas (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective. This study aims to analyze the influence of production-based learning, internships Industrial training, and parental support on entrepreneurial interest in Vocational High School (SMK) students. Method: A quantitative approach with a descriptive correlational design was used to examine the relationship between variables. Data were obtained through questionnaires, observations, interviews, and documentation, then analyzed using simple and multiple linear regression with the help of SPSS software. Result: The results of the analysis showed that each independent variable had a positive and significant influence on entrepreneurial interest. Partially, production-based learning contributed 60.5%, industrial internships 57.5%, and parental support 46.9%. Simultaneous testing showed that the three variables together contributed 64.2% to students' entrepreneurial interest. These findings indicate that learning experiences oriented towards production practices, direct involvement in the industrial environment, and emotional and motivational support from parents are important determinants in developing entrepreneurial interest. Novelty: This study concludes that production- based learning, industrial internships, and parental support are complementary factors in developing entrepreneurial orientation in vocational high school students. The practical implications of these findings emphasize the need for optimization. Teaching factory, improving the quality of industrial internships and strengthening the role of parents in supporting the entrepreneurial learning process. Further research is recommended to add other variables and expand the sample size to provide a more comprehensive picture of the factors influencing students' entrepreneurial interest.